2022
DOI: 10.1101/2022.09.21.22280189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher risk of SARS-CoV-2 Omicron BA.4/5 infection than of BA.2 infection after previous BA.1 infection, the Netherlands, 2 May to 24 July 2022

Abstract: We investigate differences in protection from previous infection and/or vaccination against infection with Omicron BA.4/5 or BA.2. We observed a higher percentage of registered previous SARS-CoV-2 infections among 19836 persons infected with Omicron BA.4/5 compared to 7052 persons infected with BA.2 (31.3% vs. 20.0%) between 2 May and 24 July 2022 (adjusted odds ratio (aOR) for testing week, age group and sex: 1.4 (95%CI: 1.3-1.5)). No difference was observed in the distribution of vaccination status between B… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…During the study period, sequentially Omicron BA.1, BA.2, BA.5 and to a lesser extent BA.4 caused the majority of the infections in the Netherlands. In previous Dutch studies, vaccine effectiveness was not significantly different between Omicron subvariants but previous BA.1 infections conferred lower protection to BA.4/5 compared to BA.2 (18,19). For infections before the study period, the variant of infection is not known for certain, and variants are highly correlated with calendar time, thus complicating disentangling effects of variants and time since infection.…”
Section: Discussionmentioning
confidence: 90%
“…During the study period, sequentially Omicron BA.1, BA.2, BA.5 and to a lesser extent BA.4 caused the majority of the infections in the Netherlands. In previous Dutch studies, vaccine effectiveness was not significantly different between Omicron subvariants but previous BA.1 infections conferred lower protection to BA.4/5 compared to BA.2 (18,19). For infections before the study period, the variant of infection is not known for certain, and variants are highly correlated with calendar time, thus complicating disentangling effects of variants and time since infection.…”
Section: Discussionmentioning
confidence: 90%
“…BA.5 evades other WT and Omicron BA.1 antibodies ( 15 17 ). Although BA.1-induced immunity is relatively less protective against BA.5, it provides some protection against reinfection with BA.2 and BA.5 ( 18 , 19 ). Our data showed that the bivalent (WT+BA.1) vaccine produced 1.5 to 2.0-fold higher NT 50 and ID 50 values against BA.5 than monovalent vaccines that were still lower than those directed against other SARS-CoV-2 variants.…”
Section: Discussionmentioning
confidence: 99%
“…hybrid immunity against SARS-CoV-2 in late 2022 1 . Especially Omicron variants have shown their potential to escape vaccine-induced humoral immunity, resulting in many vaccine breakthrough infections and the development of hybrid immunity [2][3][4][5][6][7] . Previous infection with Omicron protects against subsequent infections by other Omicron variants, and this protection may be better than hybrid immunity induced by SARS-CoV-2 variants preceding Omicron 8, 9 .…”
Section: Introductionmentioning
confidence: 99%